2002
DOI: 10.1159/000063572
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Response to Surgery and Postoperative Confusion in Depressed Patients under General Anesthesia with Fentanyl

Abstract: The purpose of this study was to investigate the relationship between postoperative confusion and plasma cortisol response to surgery in depressed patients. We studied 80 depressed patients and 40 control patients who had undergone orthopedic surgery and perioperatively measured plasma cortisol and adrenocorticotropin levels. Postoperative confusion in the first 3 postoperative days occurred in 5 (13%) depressed patients given fentanyl during anesthesia, 13 (33%) patients without fentanyl and 1 (3%) control pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It is important to consider our results in the context of the current literature. Several reports [12][13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33] have examined associations between psychiatric comorbidity and surgical patient outcomes; however, it is difficult to in- fer valid conclusions because of the heterogeneity of the studies regarding the temporal relationship of psychiatric comorbidity identified (eg, psychiatric illness identified before or after surgical admission), type of psychiatric comorbidity studied, and types of outcomes considered.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to consider our results in the context of the current literature. Several reports [12][13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33] have examined associations between psychiatric comorbidity and surgical patient outcomes; however, it is difficult to in- fer valid conclusions because of the heterogeneity of the studies regarding the temporal relationship of psychiatric comorbidity identified (eg, psychiatric illness identified before or after surgical admission), type of psychiatric comorbidity studied, and types of outcomes considered.…”
Section: Commentmentioning
confidence: 99%
“…For example, in a study of pediatric trauma patients, Gaines et al 32 found that children with a preexisting psychiatric illness had increased ICU and overall hospital-related lengths of stay and were more likely to be discharged to a location other than home. Next, in a further series of studies, Kudoh et al [12][13][14][15][16][17][18][19] examined patients undergoing abdominal and orthopedic surgery and compared a number of outcomes (eg, pain responses to analgesic agents, postoperative psychosis or confusion after anesthesia, and rates of postoperative depression after anesthesia) in cohorts with or without depression or schizophrenia. None of these studies examined mortality as an outcome.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Three reports suggested that patients with schizophrenia have more postoperative complications including death and may present at later stage of surgical disease [6–8]. Two found that pre-operative discontinuation of psychotropic medication in patients with schizophrenia or depression resulted in more postoperative delirium, confusion, and psychiatric symptoms than when medications were continued [9, 10]. The systematic review found no studies of clinical outcomes of surgery for patients with preoperative PTSD or bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline plasma cortisol concentration in depressed patients is increased [5]. We previously reported that the occurrence of postoperative confusion in depressed patients is associated with increased plasma cortisol concentrations during and after surgery [6]. Thus, plasma cortisol response to surgery appears to play animportant role in the occurrence of postoperative confusion.…”
Section: Introductionmentioning
confidence: 93%